Enquêter pour exposer - Lucie Alexis; Claire Blandin (Communication)
This article looks at a collaborative project, for master’s-level Media, Languages and Societies students at the Paris Panthéon-Assas University’s French Press Institute, on the 50th anniversary of the Bobigny trial, which created major media buzz and contributed to changes in abortion legislation. By testing gender research methods in a pedagogical context, the project sparks reflection on how pedagogical practices can be rethought by linking teaching, research, and creation. It provides an opportunity to examine the challenges of mediatizing research in the public space and articulating research themes and knowledge transmission practices in communication courses.